Efikasi Diri dan Keterlibatan Orangtua dalam Pendidikan dengan Self Regulated Learning - Andreas Yudha Fery Nugroho (Fakulatas Dakwah IAIN Salatiga, 2019)
This study aimed at determining the improvement of the quality of students who refered to several factors, namely self-regulated learning, self-efficacy and parental involvement in Education using a quantitative research approach with the Self-Efficiency scale, the scale of parental involvement in education and the scale of self-regulated learning. In this study it could be said that the ability of self-efficacy and parent involvement in education were able to predict the ability of self-regulated learning. Junior high school students realized that their abilities were supported by parents who provided assistance in the learning process would make it easier to regulate teenage learning activities.Abstrak. Penelitian ini bertujuan untuk mengetahui peningkatan kualitas pebelajar yang merujuk pada beberapa faktor yaitu self-regulated learning, efikasi diri dan keterlibatan orangtua dalam Pendidikan dengan menggunakan pendekatan penelitian kuantitatif dengan skala Efikasi Diri, Skala keterlibatan orangtua dalam pendidikan dan Skala self regulated learning. Pada penelitian ini dapat dikatakan bahwa kemampuan efikasi diri dan Keterlibatan orangtua dalam pendidikan mampu memprediksi kemampuan self regulated learning. Remaja SMP menyadari akan kemampuan yang mereka miliki didukung oleh orangtua yang memberikan bantuan dalam proses belajar akan mempermudah dalam meregulasi kegiatan belajar remaja.